Cholesterol Starvation and Hypoxia Activate the FVII Gene via the SREBP1-GILZ Pathway in Ovarian Cancer Cells to Produce Procoagulant Microvesicles - Koizume, Shiro; Takahashi, Tomoko; Yoshihara, Mitsuyo; Nakamura, Yoshiyasu; Ruf, Wolfram; Takenaka, Katsuya; Miyagi, Etsuko; Miyagi, Yohei (Thrombosis and Haemostasis, 2019)
Interaction between the transcription factors, hypoxia-inducible factor (HIF1α and HIF2α) and Sp1, mediates hypoxia-driven expression of FVII gene encoding coagulation factor VII (fVII) in ovarian clear cell carcinoma (CCC) cells. This mechanism is synergistically enhanced in response to serum starvation, a condition possibly associated with tumor hypoxia. This transcriptional response potentially results in venous thromboembolism, a common complication in cancer patients by producing procoagulant extracellular vesicles (EVs). However, which deficient serum factors are responsible for this characteristic transcriptional mechanism is unknown. Here, we report that cholesterol deficiency mediates synergistic FVII expression under serum starvation and hypoxia (SSH) via novel sterol regulatory element binding protein-1 (SREBP1)-driven mechanisms. Unlike conventional mechanisms, SREBP1 indirectly enhances FVII transcription through the induction of a new target, glucocorticoid-induced leucine zipper (GILZ) protein. GILZ expression induced in response to hypoxia by a HIF1α-dependent mechanism activates SREBP1 under SSH, suggesting reciprocal regulation between SREBP1 and GILZ. Furthermore, GILZ binds to the FVII locus. Xenograft tumor samples analyzed by chromatin immunoprecipitation confirmed that HIF1α-aryl hydrocarbon nuclear translocator and GILZ bind to the TSC22D3 (GILZ) and FVII gene loci, respectively, thereby potentially modulating chromatin function to augment FVII transcription. Thus, deficiency of both O2 and cholesterol, followed by interplay between HIFs, Sp1, and SREBP1-GILZ pathways synergistically induce fVII synthesis, resulting in the shedding of procoagulant EVs.
Keywords: hypoxia; coagulation factor VII; extracellular vesicles; SREBP1; GILZ